Peran Keluarga terhadap Penurunan Tingkat Kecemasan Lanjut Usia: The Role of Family in Reducing Anxiety Levels in the Elderly - Dewi Puspa Cipta Utami (MPI Press, 2021)
Introduction: The role of the family is the specific behavior expected by someone in the family member. Anxiety is a fear that is not clear and is not supported by the situation. Objective: to Know the Relationship of Family Role to the Level of Anxiety in the Elderly in Hamlet 01 Kukusan Beji-Depok. Method: The research method uses analytics with a cross-sectional approach. The study population was 288 people with a sample of 81 respondents using the Slovin formula. In the sampling technique using cluster sampling. Results: The results showed that the respondents with a bad family role as many as 41 (50.6%) anxiety levels of the middle-aged were 59 (72.8%). The results of statistical tests using the chi-square test indicate that there is a significant or significant relationship between the role of the family and the level of anxiety of the elderly with a value of p Value 0.01. Conclusion: It was concluded that there was a relationship between the role of the family and the level of anxiety of the elderly in the Hamlet 01 Kelurahan Kukusan Beji District Depok City.